Cortical bone thickness in different sagittal skeletal relationship: assessment and predictive modelling using artificial neural network / Nagham Mohammed Abdullah Al-Jaf - Abdullah Al-Jaf, Nagham Mohammed (2019)
Introduction: Miniscrews as anchorage devices are being increasingly used by orthodontists. Cortical thickness is a major factor affecting the success of miniscrew placement. Orthodontists treat patients with different sagittal skeletal relations. Some clinicians use three-dimensional imaging for assessment of cortical thickness for miniscrew placement. Objectives: To assess buccal cortical thickness, interradicular distance and palatal cortical thickness in different sagittal skeletal relationship. The other objective of this study was to formulate a prediction model for buccal cortical thickness without exposing patients to three-dimensional imaging and high radiation dose. Methods: Archived cone beam computed tomography (CBCT) scans of 240 adult subjects with Class I, II and III sagittal skeletal relationship and normal vertical relation were used. The scans were divided into three groups of 80 subjects with equal gender distribution. Buccal cortical thickness and interradicular distance were measured in the alveolar processes of the maxilla and mandible. The sites measured were from between central incisors to the site between the two molars. Palatal cortical thickness was also measured at nine locations. Analysis of variance (ANOVA) with post-hoc Tukey test was used with a significance level of p < 0.05 to detect differences between sagittal skeletal classes.